2021
DOI: 10.1021/acs.jchemed.1c00446
|View full text |Cite
|
Sign up to set email alerts
|

Student-Generated Infographics for Learning Green Chemistry and Developing Professional Skills

Abstract: This paper addresses the incorporation of a scaffolded infographic project into a majors' organic chemistry laboratory. Students were given the freedom to choose their topic with the stipulation that it must be relevant to both organic and green chemistry. This scaffolded project consisted of the following eight phases: (i) summarizing and evaluating an existing infographic, (ii) delving into green chemistry literature, (iii) proposing infographic topic, (iv) gathering components for the infographic, (v) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 83 publications
(122 reference statements)
1
17
0
Order By: Relevance
“…Student feedback through comments on the postsurvey (see SI, pages S27−S28) revealed that students generally appreciated interacting with other students, which agrees with the findings of the collaborative infographic assignment described by Sahai and Ivanova. 14 As highlighted by Grieger and Leontyev, 13 students greatly appreciated the hands-on experience of learning how to prepare infographics and use scientific software required for figure preparation. Notably, several students in the postsurvey described how beneficial the peer review process was, suggesting that this component of the project be emphasized.…”
Section: Examples and Dissemination Of Student Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Student feedback through comments on the postsurvey (see SI, pages S27−S28) revealed that students generally appreciated interacting with other students, which agrees with the findings of the collaborative infographic assignment described by Sahai and Ivanova. 14 As highlighted by Grieger and Leontyev, 13 students greatly appreciated the hands-on experience of learning how to prepare infographics and use scientific software required for figure preparation. Notably, several students in the postsurvey described how beneficial the peer review process was, suggesting that this component of the project be emphasized.…”
Section: Examples and Dissemination Of Student Workmentioning
confidence: 99%
“…8,9 A number of pedagogical articles have highlighted using infographics as an educational tool in a classroom setting. 10,5,11,2,12,13,3,14 However, most of these assignments were incorporated into interdisciplinary courses or foundational courses, such as organic, green, and analytical chemistry. At many colleges and universities, cellular metabolism is the central topic of second-semester biochemistry courses, 15 including the metabolism of carbohydrates, nucleic acids, and amino acids.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This need to incorporate socioscientific issues into the classroom is included in national educational standards for countries such as the USA, Germany, the UK, or Spain. 8 In the case of the Spanish curriculum, 9 objectives such as assessing scientific research and its impact on industry and the development of society, or interpreting information on scientific issues of an informative nature in publications and the media, are included. These goals show the concern of public officials in approaching novel educational tools to tackle socio-scientific issues.…”
Section: ■ Backgroundmentioning
confidence: 99%
“…The study of chemistry-related socio-scientific issues helps to improve scientific literacy and create citizens with an understanding of chemistry that can be used to improve our society. , Thus, students also learn to question, discuss aspects of chemistry, or make decisions, all of which may affect their lives and society in general. This need to incorporate socio-scientific issues into the classroom is included in national educational standards for countries such as the USA, Germany, the UK, or Spain . In the case of the Spanish curriculum, objectives such as assessing scientific research and its impact on industry and the development of society, or interpreting information on scientific issues of an informative nature in publications and the media, are included.…”
Section: Introductionmentioning
confidence: 99%